If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 1)(x + -1) = 2(5x + -5) Reorder the terms: (1 + X)(x + -1) = 2(5x + -5) Reorder the terms: (1 + X)(-1 + x) = 2(5x + -5) Multiply (1 + X) * (-1 + x) (1(-1 + x) + X(-1 + x)) = 2(5x + -5) ((-1 * 1 + x * 1) + X(-1 + x)) = 2(5x + -5) ((-1 + 1x) + X(-1 + x)) = 2(5x + -5) (-1 + 1x + (-1 * X + x * X)) = 2(5x + -5) (-1 + 1x + (-1X + xX)) = 2(5x + -5) Reorder the terms: (-1 + -1X + 1x + xX) = 2(5x + -5) (-1 + -1X + 1x + xX) = 2(5x + -5) Reorder the terms: -1 + -1X + 1x + xX = 2(-5 + 5x) -1 + -1X + 1x + xX = (-5 * 2 + 5x * 2) -1 + -1X + 1x + xX = (-10 + 10x) Solving -1 + -1X + 1x + xX = -10 + 10x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -1X + 1x + 1 + xX = -10 + 1 + 10x Reorder the terms: -1 + 1 + -1X + 1x + xX = -10 + 1 + 10x Combine like terms: -1 + 1 = 0 0 + -1X + 1x + xX = -10 + 1 + 10x -1X + 1x + xX = -10 + 1 + 10x Combine like terms: -10 + 1 = -9 -1X + 1x + xX = -9 + 10x Add '-1x' to each side of the equation. -1X + 1x + -1x + xX = -9 + 10x + -1x Combine like terms: 1x + -1x = 0 -1X + 0 + xX = -9 + 10x + -1x -1X + xX = -9 + 10x + -1x Combine like terms: 10x + -1x = 9x -1X + xX = -9 + 9x Reorder the terms: 9 + -1X + -9x + xX = -9 + 9x + 9 + -9x Reorder the terms: 9 + -1X + -9x + xX = -9 + 9 + 9x + -9x Combine like terms: -9 + 9 = 0 9 + -1X + -9x + xX = 0 + 9x + -9x 9 + -1X + -9x + xX = 9x + -9x Combine like terms: 9x + -9x = 0 9 + -1X + -9x + xX = 0 The solution to this equation could not be determined.
| 7b^2-56=49b | | 8x-1=8(x-9) | | -x(x+7)=(x-2)(x+2) | | 5(-6h-8)+(-2h+5)= | | 1/4x-1/7x=3 | | 4n-9=6-n | | 1/2x=5-1/3x | | 4(8v+4)+(6v+6)= | | (4x^3y^6z^9)2/3 | | 2(x-3)+3=2x-5 | | (-8z+7)+(-z-8)= | | 6n-3=9n+4 | | -7(-a-7)+(9a+5)= | | X=650+0.5x | | 2x+4y=4x-y | | X=0.5x+650 | | 4/5(5)(4/17) | | 8x-6=9(x-1) | | 4(5z-1)-4(z+9)=13(z+1) | | 0.6x+0.33x+12=x | | 9=x5/7=41 | | (9k-3)+4(7k+6)= | | 15x-7=13x-13 | | 1+6(x-9)=5-4(x-8) | | 5x+35=10 | | 5(2b-5)+(6b+5)= | | fx=4x^2-8x-9 | | 52x+26= | | 4(6z-1)-4(z+8)=17(z+1) | | (-f-9)+(9x+2)= | | -0.1+8.56=-0.3x+2.36 | | -3t^2+18t-4=0 |